If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6 = 13 + y Solving -6 = 13 + y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1y' to each side of the equation. -6 + -1y = 13 + y + -1y Combine like terms: y + -1y = 0 -6 + -1y = 13 + 0 -6 + -1y = 13 Add '6' to each side of the equation. -6 + 6 + -1y = 13 + 6 Combine like terms: -6 + 6 = 0 0 + -1y = 13 + 6 -1y = 13 + 6 Combine like terms: 13 + 6 = 19 -1y = 19 Divide each side by '-1'. y = -19 Simplifying y = -19
| 4x+3y=-5 | | 4z+2(3z-8)=54 | | -29=5(2a+-1)+2a | | n+5.8=11.4 | | 6x-3y=15 | | 2x+6(8x-4)=426 | | -29=5(2a-1) | | 8z+9(2z-4)=120 | | 2(3y-4)+7(6+y)=138 | | 2z(5z+10)=10z^2+20z-6 | | (-4r)(-30)-(-8)= | | 63=-3(1-2n) | | 2y+3(9y-7)=211 | | 4(2+3c)=56 | | 2x-3y=-2 | | 3(8x-4)+2(7+x)=236 | | 9+2a=2-3a | | 12z=48 | | 3(4z-6)+5(9+z)=163 | | 5(9z-3)+7(2+z)=415 | | 13-m=5 | | -128=-v-3(7v+6) | | 6+p=11 | | 8(3y-5)+9(4+y)=194 | | 3b=18 | | 4(x-1)+3=4x-(x+1) | | 4y+2(3y-5)=50 | | 3x-5(2x-1)=5x+17 | | 4(8x-9)+3(7+x)=160 | | 342=6(8-7x) | | 8z+7(4z-2)=166 | | 6(3z-7)+4(9+z)=170 |